2013
DOI: 10.1117/1.jbo.18.10.106002
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon fluorescence imaging of intracellular hydrogen peroxide with chemoselective fluorescent probes

Abstract: Abstract. We present the application of two-photon fluorescence (TPF) imaging to monitor intracellular hydrogen peroxide (H 2 O 2 ) production in brain cells. For selective imaging of H 2 O 2 over other reactive oxygen species, we employed small-molecule fluorescent probes that utilize a chemoselective boronate deprotection mechanism. Peroxyfluor-6 acetoxymethyl ester detects global cellular H 2 O 2 and mitochondria peroxy yellow 1 detects mitochondrial H 2 O 2 . Two-photon absorption cross sections for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…We have used this model to manipulate H 2 O 2 production in astrocytes (Guo et al, 2013; Haskew-Layton et al, 2010). When R. gracilis DAAO expressing astrocytes are cocultured with neurons, we found that low concentrations of peroxide production (3.7 nmol/min/mg protein) protected neighboring neurons from glutamate-induced oxidative stress, thus showing that this model can be used to distinguish protective and nonprotective concentrations of peroxide (Haskew-Layton et al, 2010).…”
Section: Production Of H2o2 Using Daaomentioning
confidence: 99%
See 4 more Smart Citations
“…We have used this model to manipulate H 2 O 2 production in astrocytes (Guo et al, 2013; Haskew-Layton et al, 2010). When R. gracilis DAAO expressing astrocytes are cocultured with neurons, we found that low concentrations of peroxide production (3.7 nmol/min/mg protein) protected neighboring neurons from glutamate-induced oxidative stress, thus showing that this model can be used to distinguish protective and nonprotective concentrations of peroxide (Haskew-Layton et al, 2010).…”
Section: Production Of H2o2 Using Daaomentioning
confidence: 99%
“…The use of conventional confocal microscopy to visualize fluorescence has limitations for real-time in vivo H 2 O 2 imaging, specifically phototoxicity, photo-bleaching, and limited imaging depth (Chen et al, 2013; Guo et al, 2013). In addition, prolonged light exposure can cause artifact ROS generation and signal amplification (Hockberger et al, 1999; Squirrell, Wokosin, White, & Bavister, 1999).…”
Section: Two-photon Fluorescence Imaging Of H2o2mentioning
confidence: 99%
See 3 more Smart Citations